Synthesis and evaluation of vitamin-drug conjugate for its anticancer activity - Bhole, R.P.; Jadhav, S.; Chikhale, R.; Shinde, Y.; Bonde, C.G. (KU Publ., 2021)
Cancer is the uncontrolled growth of cells in the human body that has the ability to spread. The purpose of the study is to explore that vitamins can be used as a targeting moiety for new anticancer drugs to address issues like non-selectivity, systemic toxicity. 5-Fluorouracil acetic acid–Vitamin D3 (5FUAC-Vit.D3) conjugate has been synthesized, characterized, and evaluated for its anticancer activity. 5-FUAC-Vit.D3 conjugate was synthesized via esterification mechanism in the presence of N-Hydroxy succinimide (NHS) and 1-(3-Dimethylaminopropyl)- 3-ethylcarbodiimide (EDC) by using HCL as coupling agent. Formation of 5-FUAC-Vit.D3 conjugate via esteric bond and the structure of the compounds were confirmed by spectroscopic data, i.e., IR, NMR, and mass spectra. The docking studies showed that 5-FUAC-Vit.D3 conjugate interacted at Arg-215 and Lys- 47 of the human thymidylate synthase proteins, through hydrogen bonding and ionic bonds respectively with a binding score of -8.614 which is higher than only 5-FU (-3.475). So, it was proved that forming 5-FUACVit. D3 conjugate shows greater binding to the target protein.
Витамин-дәрілік конъюгаттың қатерлі ісікке қарсы белсенділігін синтездеу және бағалау
Синтез и оценка конъюгата «витамин – лекарственный препарат» на предмет его противораковой активности
Keywords: synthesis; molecular modeling; molecular docking; vitamin-drug conjugate; 5-fluorouracil acetic acid; vitamin D3